2013
DOI: 10.1186/1472-6963-13-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between antenatal and postnatal care and post-partum modern contraceptive use: evidence from population surveys in Kenya and Zambia

Abstract: BackgroundIt is often assumed, with little supportive, empirical evidence, that women who use maternal health care are more likely than those who do not to use modern contraceptives. This study aims to add to the existing literature on associations between the use of antenatal (ANC) and post-natal care (PNC) and post-partum modern contraceptives.MethodsData come from the most recent Demographic and Health Surveys (DHS) in Kenya (2008–09) and Zambia (2007). Study samples include women who had a live birth withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
68
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 19 publications
25
68
3
4
Order By: Relevance
“…In our study, the longer time-to-contraceptive use observed among women who attended 1-3 ANC visits compared with those who attended the recommended four or more visits supports this finding as noted elsewhere [51]. Thus, strengthening the integration of family planning into ANC services [23,26,52,53] would certainly go a long way in promoting modern contraceptive use, particularly during the postpartum period.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our study, the longer time-to-contraceptive use observed among women who attended 1-3 ANC visits compared with those who attended the recommended four or more visits supports this finding as noted elsewhere [51]. Thus, strengthening the integration of family planning into ANC services [23,26,52,53] would certainly go a long way in promoting modern contraceptive use, particularly during the postpartum period.…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies provide insights into factors that determine contraceptive use among (i) women in the postpartum period [3,6,23,24], (ii) sexually active women in the reproductive age [20,25,26], and (iii) sexually active males [27]. However, studies are limited in providing an understanding of the factors among women particularly after resumption of sexual intercourse following a birth.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are not novel, as research has consistently shown that better educated, wealthier women, women who live in urban areas, and women who were regularly exposed to the media are all more likely to use contraception in the postpartum period (Gebreselassie et al 2008, Do andHotchkiss 2011).…”
Section: Discussionmentioning
confidence: 86%
“…[812, 24] Postpartum FP use in LMICs has also been associated with urban residence,[8] being married,[12] greater wealth and education,[1012] achievement of desired family size and current fertility desire. [24] In contrast to our study, a study conducted in five LMICs found that younger postpartum women (<20 years old) were 24% more likely than women ≥30 years to have an unmet need for FP.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Previous studies report that women who attend more antenatal care (ANC) visits, deliver with a skilled birth attendant, or attend postnatal care (PNC) are more likely to use postpartum contraception. [812] However, other factors may also impact use of FP during the postpartum period.…”
Section: 0 Introductionmentioning
confidence: 99%